Optimization of design and control parameters for an electrically-propelled aerial vehicle using the energy approach - Çiçek, İbrahim (Institute of Science and Technology, 2020)
With the recent developments in the aviation industry, the interest in green air transportation has significantly increased over the years. The possibility of green energy sources used in road and rail vehicles could help an alternative option in air transportation as well. After the first development of electrical vehicle concept, Hybrid Electric Vehicles (HEVs) and Battery Electric Vehicles (BEVs) pushed the battery technology to be improved and lead a way to be used for the aerial vehicles as well. The air transport vehicles, considering to be electrified for short-range, regional or urban operations, will depend on energy-based optimization and cost elimination for each flight cycle. The concept of electric aircraft has been studied in recent years because of their innovative appearance and zero carbon emission. Until now, unmanned, vertical or short-range take-off landing, UAV, VTOL/STOL, aerial vehicles are presented for various flight operations. The aerial vehicles powered by electrical energy or driven by e-powertrains are revealed as Electric Airplanes or Electrified Vertical Take-Off Landing Vehicles (e-VTOLs). In this study, the design optimization of the electric air vehicle is presented to develop an approach focusing on the total energy requirement for short-range flights. The developed method is based on the vehicle power consumption for a defined trip/flight profile over a required timespan. Principles of energy requirements during a trip taken into account and the design parameters are estimated. The feasible design proposal is made for short-range flights by suggesting the estimated energy requirement from battery storage. After drawing a rough picture of total energy, the corresponding battery mass, propulsion unit mass, and total vehicle mass is suggested. Since the main energy consumer is the e-motor that generates the propulsion power through powertrain elements, a detail of control parameters optimization is studied for the propulsion unit. In this regard, an online optimization method based on the Optimal Control Theory is proposed for e-motor control parameters. The widely used control method of Proportional-Integral-Derivative (PID) parameters are optimized for the selected e-motor. To come up with the set of optimum PID parameters, the Integral Squared Error (ISE) Method and Interval Halving Search Method (IHSM) are used. All estimations are made with minimum energy requirement consideration. The equations of motions and transfer functions are governed by control and stability equations by introducing the loads exerted on the vehicle. The aerodynamically generated lift and drag, the required e-motor thrust, and total vehicle weight forces during alevel flight are basically implemented.
Elektriksel tahrikli bir hava aracının enerji yaklaşımıyla tasarım ve kontrol parametreleri optimizasyonu
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2020
Keywords: aircraft; design and control; Hybrid Electric Vehicle; Unmanned Aerial Vehicle